AB1124 A uk study: vocational experiences of young adults with juvenile idiopathic arthritis. (12th June 2018) - Lunt, L.E.; Bezzant, M.; Bosworth, A.; McDonagh, J.E.; Hyrich, K.; Thomson, W.; Verstappen, S.
Abstract : Background: Little is known about the experiences of young adults living with Juvenile Idiopathic Arthritis (JIA) preparing for employment and career development. Objectives: The purpose of this study was to understand the impact JIA has on career planning and early employment experiences of young adults (16–30 years). Methods: Using existing literature (including grey literature), an online survey (consisted of 152 questions, 29 items related to young adults two of which were free text questions) was developed and sent to UK National Rheumatoid Arthritis Society (NRAS) members and distributed to non-members via social media tools including Facebook, Twitter and HealthUnlocked. Data collected included views and experiences in career planning and employment. The data pertaining to young adults are presented here. Results: Of 1241 respondents 19 were young adults with JIA (range 16–30 years), 89% were female and 84% had university or equivalent qualifications. Due to incomplete responses there is missing data on all 19 young adults. 4/13 young adults were studying at university, 9/13 were in paid employment. 9/17 respondents reported their school did not offer additional work-related activities to students with disabilities and/or additional needs. 10/14 young adults felt their school did not provide advice about coping with possible limitations on placements/traineeships due to their arthritis. 11/14 respondents did consider their condition when thinking about future career plans e.g. "I wanted to work as a ranger or similar for the National Trust but it's a fairly physically demanding job and I knew my joints would suffer so I changed track slightly". However, 8/14 felt their career advisors at school/university did not take their arthritis into account e.g. "I had to cease my physiotherapy master's degree as my arthritis got too bad to continue and change career choice. I wish there would have been more discussion about it not being a reasonable choice for me at the time as we just didn't have the information then". 8/14 young adults changed their career plans because of their arthritis with managing JIA symptoms and a physically demanding role, as well as wanting to stay healthy, being the main reasons for changing career. Important aspects of employment included: "good relationships with your line manager, work you like doing and a job you can use your initiative". Conclusions: Despite small numbers these results highlight potential current unmet vocational needs of young adults with JIA in the UK and the need for further research with this age group. There appears to be a lack of structured support within schools and universities offered to students with disabilities and/or additional needs, about work-related activities and careers. Young adults with JIA actively consider their condition whilst thinking about career opportunities and value a productive and challenging job with a good working environment, including relationships with colleagues and supervisors. Disclosure of Interest: None declared